The role of closed-loop management of fever patients in a county-level medical community for the prevention and control of the post-coronavirus disease 2019 pandemic. Issue 3 (20th January 2023) - Ding, Yajun; Xu, Chunxia; Zhang, Xingguo; He, Yanzhen; Wang, Fang; Zhang, Libo; Yu, Yaner; Zhou, Yachun; Zhang, Youping; Ye, Dongxian
Abstract : We built a closed-loop management model for patients with fever in a county-level medical community and explored the role of this model in post-coronavirus disease 2019 (COVID-19) epidemic prevention and control. The subjects included 83, 791 patients with fever treated in designated hospitals between February 2020 and April 2021. A pre-hospital, in-hospital, and post-hospital management system for patients with fever in the county-level medical community was established to allow the closed-loop management of these patients. SPSS software (version 13.0) was used to analyze the methods of visiting the hospital, nucleic acid detection in the hospital, and location of the patients after the hospital visit. Chi-square tests were used to compare the methods of visiting and location after hospital visits between patients with and without an epidemiological history. The number of patients with fever in the fever clinic showed a logarithm change ( R 2 = 0.4710), accompanied by seasonal changes. The number of fever patients with an epidemiological history decreased logarithmically monthly ( R 2 = 0.8876). Among patients with fever, 99.64% sought medical treatment on their own, with relatively low proportions undergoing home quarantine and requiring centralized quarantine special vehicles. After visiting the fever clinics, 98.56% of patients isolated at home or were monitored, with small proportions of patients requiring hospital admission or centralized isolation. However, the proportions of patients with home and centralized isolation with epidemiology were relatively high, accounting for 20.55% and 27.40% of cases, respectively. Compared to the overall population of patients with fever, the difference was statistically significant ( χ 2 = 48.881, P = .000). The establishment of a closed-loop management model for patients with fever in a county-level medical community strengthened the management of these patients. No local cases occurred in Beilun District between March 2020 and April 2021. In the post-COVID-19 era, all medical institutions in the county-level medical community strengthened infectious disease pre-examination and triage and promoted the formation of a strategic pattern of initial diagnosis at the grassroots level, 2-way referral, upper and lower linkage, and joint epidemic prevention. This management was more conducive to COVID prevention and control by hierarchical management according to the presence or absence of an epidemiological history.